2020
DOI: 10.1645/19-66
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Confirmation of a Fasciola Gigantica × Fasciola Hepatica Hybrid in a Chadian Bovine

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…In areas where both species coexist, F. hepatica x F. gigantica hybrids have been found [31][32][33]. Recently, the presence of hybrids has also been confirmed in sub-Saharan Africa [34]. Fascioliasis is endemic in West Africa with the predominant species being F. gigantica [35,36].…”
Section: Introductionmentioning
confidence: 98%
“…In areas where both species coexist, F. hepatica x F. gigantica hybrids have been found [31][32][33]. Recently, the presence of hybrids has also been confirmed in sub-Saharan Africa [34]. Fascioliasis is endemic in West Africa with the predominant species being F. gigantica [35,36].…”
Section: Introductionmentioning
confidence: 98%
“…However, the traditional morphological methods used to distinguish the two species may be unreliable, especially in the presence of hybrids that result in intermediate forms in endemic areas where the two species overlap [14]. Previous reports have shown that genetic hybridization can be detected in Fasciola species using the ribosomal internal transcribed spacer (ITS) region and mitochondrial DNA as genetic markers [4,14]. In Vietnam, a report, which analyzed 14 samples extracted from humans, presented the majority of F. gigantica (9/14).…”
Section: Discussionmentioning
confidence: 99%
“…The development of molecular methods enables specieslevel identification and provides a powerful tool for identifying potential hybrid species [3]. Currently, there have been several reports of a hybrid of F. hepatica and F. gigantica in animals worldwide [4]. However, this liver fluke has rarely been detected in humans.…”
Section: Introductionmentioning
confidence: 99%
“…A study in Niger also showed that 66.7% of 12 cattle isolates were F. gigantica (Ali et al 2008). In the past, it was believed that F. hepatica was present primarily in the temperate regions, while F. gigantica is distributed in some countries in tropical region (Evack et al 2020). This has been proved not to be the case because several , including this present study that have shown the existence of both F. hepatica and F. gigantica in the three localities in Kenya.…”
Section: Discussionmentioning
confidence: 99%